Eccentric and Concentric Motion of Hamstring during the Leg Curl - Thapa, Shiva Bikram; Basnet, Suresh; Khanal, Raju (Journal of Institute of Science and Technology, 2021)
The force experienced by the hamstring during the leg curl has been numerically investigated using the conservation theorem. The center of the meniscus is assumed to be the pivot point along with the uniform distribution of forces in the frictionless environment. The variation of force experienced by the hamstring during the concentric motion of the leg curl has been derived and graphically illustrated. It is found that the force experienced by the hamstring increases with the increase in length of the lower leg and its weight as well. The magnitude of force decreases with the increase in distance from the pivot to insertion. However, the magnitude of force increases from about 3.60 to 4.79 kN in the practically valid region 3 to 4 cm distance from the pivot to insertion with the increase in weight of lower leg from 5 to 15 kg. On the other hand, the magnitude of force increases from about 3.75 to 9.80 kN with the increase in weight suspended on the machine from 10 to 40 kg. In addition, the force decreases with the increase in upper leg dimension, but it linearly increases with the increase in the angle of suspension.